Lack of junctional adhesion molecule (JAM)-B traps CD8 T cells in CNS border zones and ameliorates autoimmune neuroinflammation - Javier Pareja; Sidar Aydin; Mara Zbinden; Elisa Bouillet; Niklas Zollinger; Vidusiya Theivendram; Amal Fahmi; Petr Pleskač; Sara Barcos; Felix Paas; Florencia Kloster; Aida Muñoz Blázquez; et al. (Acta Neuropathologica Communications)
Abstract The endothelial blood-brain barrier (BBB) tightly controls T cell entry into the central nervous system (CNS). T cell extravasation across the BBB involves a multi-step cascade with a predominant role of α4β1-integrins. In contrast to CD4 T cells, α4β1-integrin mediated CD8 T cell interaction with the BBB was proposed to involve the tight junction protein junctional adhesion molecule (JAM)-B. Here, we made use of ODC-OVA mice expressing ovalbumin as neo-self-antigen in oligodendrocytes that is solely visible to CD8 T cells, allowing to investigate CD8 T cell-mediated autoimmune neuroinflammation. We generated JAM-B-deficient ODC-OVA mice (ODC-OVA; JAM-BKO mice) and compared CD8 T cell mediated autoimmune neuroinflammation to their ODC-OVA; JAM-BWT littermates. ODC-OVA; JAM-BKO mice developed ameliorated clinical disease, which was associated with a marked reduction in CD8 T cell infiltration into the CNS parenchyma. Surprisingly, lack of JAM-B did not affect CD8 T cell arrest or extravasation in spinal cord microvessels but rather resulted in CD8 T cell accumulation in the subarachnoid space and perivascular spaces in ODC-OVA; JAM-BKO mice. Detection of Jam-2 RNA expression in cells other than BBB endothelial cells contributing to CNS barriers including astrocytes forming the glia limitans, Bergmann glial cells, meningeal fibroblasts and choroid plexus epithelial cells suggests that JAM-B may regulate CD8 T cell entry into the CNS at barriers other than the BBB, particularly at the glia limitans. Thus, targeting JAM-B could provide a therapeutic strategy for treating neuroinflammation without disrupting T cell-mediated immune surveillance in CNS border compartments.